Prediction of the Henry Law Constants for Vapours of Organic Molecules of the Rigid Pivot Type - V.V. Kutarov; B.M. Kats (Adsorption Science & Technology)
Henry law adsorption constants have been predicted a priori on the basis of the Corresponding States Principle. A two-dimensional model was used which gave proportionality between the critical pressure in the condensed phase and the saturation pressure of reference and test molecules of the rigid pivot type. The potential applicability of the suggested method was tested using known experimental data for methane and the calculated values of the two-dimensional critical pressures of ethane, propane and n-butane. For small alkanes, the two-dimensional critical pressure values can be readily estimated on the basis of their two-dimensional van der Waals constants and the distribution function of molecules vertically and horizontally oriented to the adsorption surface.